Reliability of the Endoscopic Ultrasound Ulcerative Colitis (EUS-UC) score for assessment of inflammation in patients with ulcerative colitis - Yan, Brian M.; Sey, Michael S.L.; Belletrutti, Paul; Brahm, Gary; Guizzetti, Leonardo; Jairath, Vipul (Endoscopy International Open, 2021)
Background and study aims Endoscopic ultrasound (EUS) may be a useful modality for disease assessment and risk stratification in ulcerative colitis. We assessed the reliability of a newly developed EUS index of inflammation called the EUS-Ulcerative Colitis (EUS-UC) score.Patients and methods The EUS-UC score components include total wall thickness, hyperemia, and depth of inflammation (DOI). Three blinded expert endosonographers assessed EUS videos of 58 patients with UC in triplicate. Intra- and inter-rater reliability of the hyperemia and DOI component scores were estimated using intra-class correlation coefficients (ICCs). Total wall thickness reliability estimates could not be assessed in this study. The ICCs were compared to the original indices from which they were derived.Results For hyperemia, the inter-class ICC was “moderate” at 0.556 (95 % CI = 0.434–0.651) and the intra class ICC was “almost perfect” at 0.884 (95 % CI = 0.835–0.920). The newly defined hyperemia score performed better than the original index from which is was derived. The DOI inter-class ICC was “fair” at 0.335 (95 % CI = 0.201–0.464), and the intra-class ICC was “substantial” at 0.732 (95 % CI = 0.642–0.802). The DOI reliability estimates were similar to the original index from which it was derived.Conclusions The hyperemia component of the EUS-UC score performed significantly better than the original index from which it was derived, but the reliability of the DOI component was suboptimal. Intra-class correlation was excellent for both components. The EUS-UC score is a promising instrument for assessment of UC and further validation is required.